Subject modality in A.S. Grin’s story “Island Reno” - Мусий, Валентина Борисовна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article deals with the embodied in the story by A.S. Grin author’s conception of the human being. The story is based on the binary opposition “own – alien”, which helps the writer to express not only his rejection of reality, in which a person loses freedom and spontaneity and in which lacks creativity, but his idea of human impossibility for stand-alone status from community. The hero of the story makes his choice between the old “dark” life and unite with the nature, but his harmony with the world of nature is short-lived and ends with his death. Study of subjective modality (point of view on the events of the hero) helps to understand the author’s idea.